Beeinflussung der 201TI-SPECT des Myokards durch die Mamma-Absorption - Bockisch, A.; Ruhlmann, J.; Hotze, A.; Biersack, H.-J. (Nuklearmedizin - NuclearMedicine, 1989)
The attenuation effect of the female breast on single-photon emission computed 201TI-chloride myocardial tomograms (SPECT) was quantitatively evaluated in a group of 20 women. SPECT was carried out with the left breast in the normal position and after its maximal upward displacement. The count rate gain was up to 30% when the breast was raised. 201TI-chloride myocardial SPECT often showed false lesions in the anterior wall which resulted from the attenuation of the gamma rays by the female breast. This factor is neglected in constructing the tomograms, and even if such artifacts are absent, the attenuation may adversely affect the calculated wash-out values.